Copper wire bond improvement on aluminum interface for optimum high emperature storage reliability performance - Wong, Jia Yi (2021)
Copper wire bonding has becoming popular as semiconductor packaging interconnect method due to its advantages over gold wire. Lower cost, better conductivity and lower resistivity are the main factors. Copper wires are harder than gold wire, therefore higher ultrasonic power and bond force require for copper wire bonding compare to gold wire bonding. Although the intermetallic growth between copper wire on aluminium is much slower than gold wire on aluminium, the kirkendall void is still a concern at high temperature storage test (HTSL). Addressing it has becoming more challenging due to the stringent requirement from the Joint Electron Device Engineering Council (JEDEC). JEDEC has published new qualification standard for Automotive Electronic Council (AEC) Q006 for copper wire qualification. HTSL is the most critical reliability test where intermetallic growth mechanism is accelerated by high temperature. The new HTSL standard request for higher temperature at 175 ºC with 1000 hours duration has high impact to the bond integrity compare to the old requirement at 150 ºC. As such, it is crucial to improve the bond power and bond force in timely manner, in order to pass the qualification for the new product time to market. The purpose of this research is to develop a robust wire bond process window, that is bond power and bond force to fulfil the HTSL requirement. The optimum wire bond process window identified from the response surface model DOE are bond power: 73-87 DAC and bond force: 64-76 gram. From the window corner validation DOE, the ball pull, ball shear, aluminum metal remain thickness intermetallic (IMC) coverage area successfuly passed the specification and process capability index >2.0, proven to be robust setting without overbond cratering issue. When the bond power and bond force increased, the ball shear force and intermetallic coverage area increased, and the aluminum metal remain thickness reduced. There are no correlation between bond pull force with bond power and bond force identified. The new bond power and bond force process parameter window validation has successfully passed HTSL at 175 ºC with 1000 hours thermal aging, with no sign of degradation based on the ball shear, ball pull and cross section IMC phase growth. To ensure the cleanliness of the aluminum bond pad surface, additional bond pad scrubbing before wire bonding is proven to be effective for intermetallic coverage area improvement. This guaranteed good wire bond adhesion on the bond pad in order to survive through HTSL stress condition.